Treinamento prescrito pela velocidade pico e velocidade referente à ocorrência do consumo máximo de oxigênio para corredores de endurance moderamente treinados - Manoel, Francisco de Assis (2016)
Endurance running training programs require an adequate stimulus according to the physical condition of each practitioner. The peak velocity (Vpeak) has proven to be an excellent predictor of performance; but, it is necessary to test its applicability in prescribing training. The objective of the study was to evaluate the effect of four weeks of training prescribed by the Vpeak and velocity corresponding to the occurrence of maximum oxygen consumption (vVO2maX) in moderately trained endurance runners. Study participants were 16 runners aged between 18 and 35 years who were randomized into two groups. One group held four weeks of training prescribed by vVO2maX and its respective time limit (tum) (GVO2) and another held training prescribed by Vpeak and its respective tum (GVP). Four tests on a treadmill were performed: two maximum incremental tests to determine the Vpeak and vVO2maX and two for the determination of their tum, and a performance of 10 km in official running track (400 m). All initial evaluations were also conducted after a period of four weeks of training. Participants performed a total of 20 race training sessions, divided into continuous and inter al training sessions. The variables are presented as mean i standard deviation (SD). Data normality was verified by the Shapiro-Wilk test. The comparison between the pre- and post-training for the two groups was made by mixed ANOVA for repeated measures. Correlations between aerobic and anaerobic parameters with 10-km running performance were performed using the Pearson correlation coefficient. The significance level was set at P < 0.05. The main results showed a significant effect of training on the variables for the same group: Vpeak GVP (16.7 ± 1.2 vs 17.6 ± 1.5 km'h"), GVO2 (17.1 I 1.9 vs 17.7 ±1.6 km°h"); vVO2maX GVP (16.4 ± 1.4 vs 17.0 ± 1.3 km'h'?), GVO2 (17.2 ± 1_7 vs 17.5 1 1.9 km'h"); the time to complete 10-km GVP (41.3 ± 2.4 vs 39.9 ± 2_7 min), GVO2 (40.1 ± 3.4 vs 39.2 2.9 min) end 10-km average speed (VIVI) GVP ( 14.6 ± 0.9 vs 15.1 ± 1.1 km'h") GVO2 (15.1 ± 1.3 vs 15. ± 4 1.2 km'h"). The Vpeak showed a high correlation with the performance in both pre and post-training times GVP (r = -0.97 vs 0.86) and GVO2 (r = -0.95 vs -0.94), which was also obser ed for vV()2maX GVP (r = - 0.82 vs -0.88) and GVO2 (r = -0.99 vs -0.98). The VO2maX, tum at Vpeak, and vVO2maX did not correlate with the performance of 10 km. There was no significant difference for the variables maximal oxygen uptake (VO2maX), tum at Vpeak and vVO2maX, maximum heart rate (HRMX), mean heart rate (HRmean), rating of perceived exertion (RPEmaX), lactate peak (Lacpeak) in both groups after the training period and there was also no difference between the GVP and GVO2 for all variables. lt is concluded that the training prescribed by Vpeak promoted similar improvements to the training prescribed by vVO2maX in moderately trained endurance runners. Thus, we suggest the use of Vpeak for prescribing and monitoring endurance training, due to its practical application and low cost (i.e., no need for high cost of equipment (gas ana yzer)) for its determination.